The design and conduct of a pragmatic cluster randomized trial of an advance care planning program for nursing home residents with dementia. (December 2022) - Hickman, Susan E; Mitchell, Susan L; Hanson, Laura C; Tu, Wanzhu; Stump, Timothy E; Unroe, Kathleen T
Background/Aims: A significant number of people with Alzheimer's disease or related dementia diagnoses will be cared for in nursing homes near the end of life. Advance care planning (ACP), the process of eliciting and documenting patient-centered preferences for care, is considered essential to providing high quality care for this population. Nursing homes are currently required by regulations to offer ACP to residents and families, but no training requirements exist for nursing home staff, and approaches to fulfilling this regulatory and ethical responsibility vary. As a result, residents may receive care inconsistent with their goals, such as unwanted hospitalizations. Pragmatic trials offer a way to develop and test ACP in real-world settings to increase the likelihood of adoption of sustainable best practices. Methods: The "Aligning Patient Preferences—a Role Offering Alzheimer's patients, Caregivers, and Healthcare Providers Education and Support (APPROACHES)" project is designed to pragmatically test and evaluate a staff-led program in 137 nursing homes (68 = intervention, 69 = control) owned by two nursing home corporations. Existing nursing home staff receive standardized training and implement the ACP Specialist program under the supervision of a corporate lead. The primary trial outcome is the annual rate of hospital transfers (admissions and emergency department visits). Consistent with the spirit of a pragmatic trial, study outcomes rely on data already collected for quality improvement, clinical, or billing purposes. Configurational analysis will also be performed to identify conditions associated with implementation. Results: Partnerships with large corporate companies enable the APPROACHES trial to rely on corporate infrastructure to roll out the intervention, with support for a corporate implementation lead who is charged with the initial introduction and ongoing support for nursing home-based ACP Specialists. These internal champions connect the project with other company priorities and use strategies familiar to nursing home leaders for the initiation of other programs. Standardized data collection across nursing homes also supports the conduct of pragmatic trials in this setting. Discussion: Many interventions to improve care in nursing homes have failed to demonstrate an impact or, if successful, maintain an impact over time. Pragmatic trials, designed to test interventions in real-world contexts that are evaluated through existing data sources collected routinely as part of clinical care, are well suited for the nursing home environment. A robust program that increases access to ACP for nursing home residents has the potential to increase goal-concordant care and is expected to reduce hospital transfers. If successful, the ACP Specialist Program will be primed for rapid translation into nursing home practice to reduce unwanted, burdensome hospitalizations and improve the quality of care for residents with dementia.